The Influence of Foot Massage and Warm Water Soaking on Leg Oedema of Third Trimester Pregnant Woman: Pengaruh Pijat Dan Rendam Kaki Dengan Air Kencur Hangat Terhadap Oedema Kaki Pada Ibu Hamil Trimester III - Pretika Sri Wahyuningsih; Rini Hariani Hatih; Yusmaharani Yusmaharani (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Edema occurs in about 80% of pregnancies. Edema that often occurs in pregnancy is leg edema. Soaking feet in warm water with kencur is a non-medical action that can be performed on pregnant women. To determine the effect of massage and soaking feet with warm kencur water on leg edema in third trimester pregnant women. This type of research is Quasy Experiment. The design used is One Group Pre Test and Posttest. This research was conducted at the Guava Mawar Pratama Clinic in February-May 2023. The tools and materials used were olive oil, kencur and observation sheets. The population in this study were 13 respondents. Sampling used Quata sampling, namely a sampling technique based on the criteria set by the researcher. Sources of data used are primary data and secondary data. Data analysis used univariate and bivariate before carrying out the bivariate test parametric test, namely the normality test of normally distributed data using the T-Dependent test. There is an effect of foot massage and foot soaking with warm kencur water on leg edema in third trimester pregnant women. Significance value <0.005 with P value = 0.001 (Ha accepted). There is an effect of massage and soaking feet with warm kencur water on foot edema in third trimester pregnant women at the Jambu Pratama Clinic